Climate change 2022 mitigation of climate change : Working Group III Contribution to the Sixth Assessment Report of the Intergovernmental Panel on Climate Change - Shuka, Priyadarshi R. (Cambridge University Press, 2023)
This Working Group III contribution to the IPCC Sixth Assessment Report provides a comprehensive and transparent assessment of the literature on climate change mitigation. The report assesses progress in climate change mitigation options for reducing emissions and enhancing sinks. With greenhouse gas emissions at the highest levels in human history, this report provides options to achieve net zero, as pledged by many countries. The report highlights for the first time the social and demand-side aspects of climate mitigation, and assesses the literature on human behaviour, lifestyle, and culture, and its implications for mitigation action. It brings a wide range of disciplines, notably from the social sciences, within the scope of the assessment. IPCC reports are a trusted source for decision makers, policymakers, and stakeholders at all levels (international, regional, national, local) and in all branches (government, businesses, NGOs). Available as Open Access on Cambridge Core.